2015
DOI: 10.1016/s2095-3119(14)60857-1
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a novel UDP-glycosyltransferase gene induced by DON from wheat

Abstract: Fusarium head blight, caused primarily by Fusarium graminearum, is a destructive disease of wheat throughout the world. However, the mechanisms of host resistance to FHB are still largely unclear. Deoxynivalenol (DON) produced by F. graminearum which enhances the pathogen to spread could be converted into inactive form D3G by UDP-glycosyltransferases (UGTs). A DON responsive UGT gene, designated as TaUGT4, was first cloned from wheat in this study. The putative open reading frame (ORF) of TaUGT4 was 1386 bp, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Fluorescence observation revealed that TaUGT6 was distributed throughout cells including in cell membrane and nuclei, similar to that in pA7-eGFP (Figure 3). Its subcellular localization was similar to that reported for TaUGT3 but different from those reported for TaUGT4 and TaUGT5 (Ma et al, 2010(Ma et al, , 2015Zhao et al, 2018).…”
Section: Subcellular Localization Of Taugt6supporting
confidence: 69%
See 3 more Smart Citations
“…Fluorescence observation revealed that TaUGT6 was distributed throughout cells including in cell membrane and nuclei, similar to that in pA7-eGFP (Figure 3). Its subcellular localization was similar to that reported for TaUGT3 but different from those reported for TaUGT4 and TaUGT5 (Ma et al, 2010(Ma et al, , 2015Zhao et al, 2018).…”
Section: Subcellular Localization Of Taugt6supporting
confidence: 69%
“…In wheat, few UGT genes have been identified and proven to be functional in FHB resistance. TaUGT1 was repressed, and TaUGT2 and TaUGT4 with high similarity to HvUGT13248 were induced after F. graminearum inoculation, but no further functional analysis was conducted (Lin et al, 2008;Ma et al, 2015). Thus far, only TaUGT3, TaUGT5, and Traes_2BS_14CA35D5D (orthologous to Bradi5g03300) in wheat have been transformed into plants to prove their role in FHB resistance and DON tolerance (Gatti et al, 2018;Xing et al, 2018;Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently the HvUGT-10 W1 gene isolated from an FHB resistant barley variety (10 W1) also conferred FHB tolerance [ 34 ]. In wheat only a few candidate UGT genes such as TaUGTB2 , TaUGT1 , TaUGT2 , TaUGT3 , TaUGT4 , and TaUGT12887 have been identified and the later 4 genes have been shown to be closely related to FHB resistance; however, a large scale systematic investigation of UGTs in the wheat genome is still lacking [ 35 39 ].…”
Section: Introductionmentioning
confidence: 99%